Complex postglacial recolonization inferred from population genetic structure of mottled sculpin Cottus bairdii in tributaries of eastern Lake Michigan, U.S.A. Issue 5 (12th September 2016) - Homola, J. J.; Ruetz, C. R.; Kohler, S. L.; Thum, R. A.
Abstract : This study used analyses of the genetic structure of a non‐game fish species, the mottled sculpin Cottus bairdii to hypothesize probable recolonization routes used by cottids and possibly other Laurentian Great Lakes fishes following glacial recession. Based on samples from 16 small streams in five major Lake Michigan, U.S.A., tributary basins, significant interpopulation differentiation was documented (overall F ST = 0·235). Differentiation was complex, however, with unexpectedly high genetic similarity among basins as well as occasionally strong differentiation within basins, despite relatively close geographic proximity of populations. Genetic dissimilarities were identified between eastern and western populations within river basins, with similarities existing between eastern and western populations across basins. Given such patterns, recolonization is hypothesized to have occurred on three occasions from more than one glacial refugium, with a secondary vicariant event resulting from reduction in the water level of ancestral Lake Michigan. By studying the phylogeography of a small, non‐game fish species, this study provides insight into recolonization dynamics of the region that could be difficult to infer from game species that are often broadly dispersed by humans.